2014
DOI: 10.1373/clinchem.2013.209676
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Oral Fluid in Antidoping Testing

Abstract: BACKGROUND Currently, urine and blood are the only matrices authorized for antidoping testing by the World Anti-Doping Agency (WADA). Although the usefulness of urine and blood is proven, issues remain for monitoring some drug classes and for drugs prohibited only in competition. The alternative matrix oral fluid (OF) may offer solutions to some of these issues. OF collection is easy, noninvasive, and sex neutral and is directly observed, limiting potential adulteration, a major problem for urine testing. OF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 70 publications
(112 reference statements)
0
50
0
4
Order By: Relevance
“…, not in a clinical–laboratory setting). Examples include therapeutic drug monitoring, pain management programs [1,5,6], anti-doping controls [2], and roadside or workplace drug testing [4,5,7,8]. Major advantages of oral fluid analysis include these features: (i) non-invasive, (ii) sex-neutral ( i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, not in a clinical–laboratory setting). Examples include therapeutic drug monitoring, pain management programs [1,5,6], anti-doping controls [2], and roadside or workplace drug testing [4,5,7,8]. Major advantages of oral fluid analysis include these features: (i) non-invasive, (ii) sex-neutral ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Major advantages of oral fluid analysis include these features: (i) non-invasive, (ii) sex-neutral ( i.e. , common to male and females), (iii) directly observable sample collection (unlike urine testing), and (iv) reduced biohazard risks [2,6]. On the other hand, drawbacks are the limited fluid volume that can be collected rapidly [4,5] and the instability of some drugs in oral fluid.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] The authors also describe the advantage of LC-MS/ MS compared to immunoassay in relation to sensitivity. [53] In this context Keevil et al have shown that testosterone is almost stable for several days at room temperature as well as stable after several freeze-thaw cycles, supporting the focus on saliva in doping analysis. [52] In sum, there are many arguments for focusing on salivary analysis in the fight against doping.…”
Section: Hormone Quantificationmentioning
confidence: 89%
“…21 In case of administration of DHEA, which is considered as a prohormone of T, the analysis of T and its metabolites leads to positive results in the same way as direct analysis of DHEA. [25][26][27] Ponzetto et al 28 Saliva samples were collected after T gel application and the concentration of T was clearly above the intra-individual reference threshold, enabling the detection of T application for 76 hours. [25][26][27] Ponzetto et al 28 Saliva samples were collected after T gel application and the concentration of T was clearly above the intra-individual reference threshold, enabling the detection of T application for 76 hours.…”
Section: Introductionmentioning
confidence: 99%